Sistema de información web para mejorar los procesos en el área de servicio de postventa de la Empresa Autonort Trujillo s.a - Gonzales Sandoval, Rosa María (2019)
The present research work entitled "Web Information System to improve processes in the Post-Sales Service Area of the Autonort Trujillo SA Company" Its purpose is to ensure that the After Sales Service has better control, handling and quick consultation of the information. As well as the reduction of time on the processes of record of appointments and attention of the appointments, since the client will be a user and will be able to see through the web information about his appointment, the maintenance of his vehicles and when they are ready for his delivery. Also, after-sales service allows automotive agencies to know the opinion of customers, identify opportunities for improvement and evaluate products and processes. However, a poor after-sales service can negatively affect the clients' points of view and reduce sales levels. Thus, having technology as a main tool will replace what is currently being developed manually. The general design of this research is of the Quasi-Experimental type (Pre-Test and Post-Test). Surveys, interviews, and observation were used as a data collection technique. Open and closed questions were formulated for the different interviewees (Assistants, Service Advisors and Clients). And for the testing of the hypothesis two types of statistical tests were used, for the qualitative indicators the Student t Distribution was used, and for the quantitative indicators the Normal Distribution Z; for modeling the RUP methodology was used and for developing technology Asp.net, C # language and JavaScript, IIS and database manager SQL Server Management Studio. With the implementation of the Web Information System it will be possible to significantly increase the levels of customer satisfaction, reduce the times in the search for information of the appointment, reduce the times used by the service advisors in attending the Appointment and in generating an workorder.